(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This research highlights the unlimited influence of Persians on the Arab states as well as their effect on the intellectual, Cultural, political and social domains. The study also focuses on Translation by Persians and its stylistics and significance as an intellectual reproduction of literary works and human thought. The research then introduces the life of the poet Baba Taher Al-Arian Al-Hamathani , and the definition of his Rubaiyat in terms of form, rhyme and themes. The research also highlights the experience of poet Saleh Al-Ja’afari in translating this work, and the challenges he has faced, and provides an overview of the experience of Dr. Muhammad Nour Al-Deen Abd Al-Mun’em’s translation of Al Ruba’iyat. The study caries out an examination, analysis and verification of ten translations of the work among ten translators. Ten translations of the Ruba’iyat have been examined, whereby its Persian origin has been verified and confirmed in the study and the translation, and also in the footnotes provided. The study highlighted the stylistic, syntactic and semantic mistakes in these translations based on the two translations of poet Saleh Al-Ja’afari and Nour Al-Deen Abd Al-Mun’em. The study has been valuable to the researcher in terms of additional experience added to his repertoire.